Answer:
The correct answer is z = -6.
Explanation:
1/3 (2z + 6) = 1/4 (z - 2)
The first step I am going to take is to multiply both sides of the equation by 12 (the least common multiple of 3 and 4). This will eliminate the fractions on both sides of the equations and make the numbers much easier to work with.
4 (2z + 6) = 3 (z - 2)
Next, we can use the distributive property to eliminate the parentheses. This means multiplying each term inside the parentheses by the coefficient on the outside of the parentheses.
8z + 24 = 3z - 6
Now, we can subtract 3z from both sides of the equation.
5z + 24 = - 6
Next, we should subtract 24 from both sides of the equation.
5z = -30
Finally, we can divide both sides of the equation by 5.
z = -6
Therefore, the correct answer is z = -6.
Hope this helps!